2019
DOI: 10.1038/s41598-019-56156-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific effects of transthyretin on neural stem cell fate in the subventricular zone of the adult mouse

Abstract: Choroid plexus epithelial cells produce and secrete transthyretin (TTR). TTR binds and distributes thyroid hormone (TH) to brain cells via the cerebrospinal fluid. The adult murine subventricular zone (SVZ) is in close proximity to the choroid plexus. In the SVZ, TH determines neural stem cell (NSC) fate towards a neuronal or a glial cell. We investigated whether the loss of TTR also disrupted NSC fate choice. Our results show a decreased neurogenic versus oligodendrogenic balance in the lateroventral SVZ of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…This discrepancy between mRNA and protein expressions can be explained by a longer half-life of both THT proteins, as previously observed in rats ( Wittmann et al., 2015 ). Similarly, we previously demonstrated that Ttr transcripts are expressed in the SVZ of adult mice, whereas the protein is not detected by IHC ( Vancamp et al., 2019 ).
Figure 2 TH Signaling Components Are Dynamically Expressed in Neuronal Lineage Cells within the Adult SVZ (A) Schematic representation of the markers used to quantify TH signaling components mRNA expression levels in quiescent and activated NSCs (CD133+EGFR), TACs (EGFR+), NPCs (EGFR+CD24+) and neuroblasts (CD24+) from FACS-sorted SVZ cells of five adult WT male mice.
…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…This discrepancy between mRNA and protein expressions can be explained by a longer half-life of both THT proteins, as previously observed in rats ( Wittmann et al., 2015 ). Similarly, we previously demonstrated that Ttr transcripts are expressed in the SVZ of adult mice, whereas the protein is not detected by IHC ( Vancamp et al., 2019 ).
Figure 2 TH Signaling Components Are Dynamically Expressed in Neuronal Lineage Cells within the Adult SVZ (A) Schematic representation of the markers used to quantify TH signaling components mRNA expression levels in quiescent and activated NSCs (CD133+EGFR), TACs (EGFR+), NPCs (EGFR+CD24+) and neuroblasts (CD24+) from FACS-sorted SVZ cells of five adult WT male mice.
…”
Section: Resultsmentioning
confidence: 58%
“…This discrepancy between mRNA and protein expressions can be explained by a longer half-life of both THT proteins, as pre-viously observed in rats (Wittmann et al, 2015). Similarly, we previously demonstrated that Ttr transcripts are expressed in the SVZ of adult mice, whereas the protein is not detected by IHC (Vancamp et al, 2019).…”
Section: The Th Signaling Pathway Is Dynamically Regulated During Neumentioning
confidence: 61%
See 1 more Smart Citation
“…Notum, a secreted extracellular suppressor of Wnt ligands, displays SVZ-subdomain-specific expression [180], raising an interesting possibility of spatially-restricted regulation of Wnt pathway activation via localized deactivation of Wnt ligands, which were previously shown to be secreted from the CP into CSF [62,111]. Corroborating these findings, transthyretin (TTR), a thyroid hormone transporter predominantly produced by the CP [112], exhibits a gender-specific role in the control of neurogenesis in the SVZ that is restricted to a specific subdomain of the SVZ [181], which is in line with the gender-based differences in CP-derived TTR levels detected in the CSF [71,182]. Molecular heterogeneity linked to the receptor repertoire can be also observed between SVZ and SGZ, indicating intrinsic differences in the sensitivity of adult germinal centres to signalling factors presented via CSF [183,184].…”
Section: The Target Brain Regions Of Cp-csf Signallingmentioning
confidence: 93%
“…Data on the regulation of TH metabolism in NSCs almost exclusively originates from rodent studies. MCT8 and OATP1C1 mediate TH uptake at the endothelial cells of the rodent BBB as they do in other brain regions ( Mayerl et al, 2014 ; Vatine et al, 2017 ), while TTR provides at least a part of T 4 to SVZ-NSCs via the CSF ( Vancamp et al, 2019 ; Alshehri et al, 2020 ). It is currently unknown which transporters facilitate TH uptake into SVZ-NSCs themselves.…”
Section: The Potential Of Thyroid Hormone As a Pro-repair Cuementioning
confidence: 99%